An Economic Analysis of Watershed Development Project in Udaipur District of Rajasthan - Jain, Ashvini Kumar; Burark, S S; Pant, D C; Jain, H K (Annals of Arid Zone, 2016)
The study conducted on Watershed Development Project in Mavli Panchayat of Udaipur District showed that the maximum percentage increase in net income (36.7%) was for marginal beneficiary farmers followed by small (27.23%), medium (7.66%) and large beneficiary (7.48%) farmers. The IWDP helped to increase the consumption expenditure, which was minimum on large farms (Rs. 2187 per annum) and maximum on medium farms (Rs. 6506 per annum). The relative increase in consumption expenditure for different categories of beneficiary families was not similar. The same was true for expenditure on various components like food, clothing, education, fuel, building and others. The absolute and per cent increase in annual employment was observed on all the categories of beneficiary farmers. Key words: Beneficiaries, income, consumption, employment, IWDP, NWDPRA